Digital Culture & Education (2010)
Digital Culture & Education (DCE) is an international inter-disciplinary peer-reviewed journal dedicated to the exploration of digital technology$1 (Bs impacts on identity, education, art, society, culture and narrative within social, political, economic,s
cultural and historical contexts.We are interested in empirical and conceptual approaches to theorising globalisation, development, sustainability, wellbeing, subjectivities, networks, new media, gaming, multimodality, literacies and related issu
es and their implications for how we educate and why. We encourage submissions in a variety of modes and invite guest editors to propose special editions.DCE is an online, open access journal. It does not charge for article submission or for publi
cation. All manuscripts submitted to DCE are double blind reviewed. Articles are published through a Creative Commons (CC) License and made available for viewing and download on a bespoke page at www.digitalcultureandeducation.com